Akuntabilitas Pengelolaan Dana Desa - Cahyana, Pande Gede; Suprasto, Herkulanus Bambang (E-Jurnal Akuntansi, 2023)
Management of village funds is required to implement the principles of good governance and accountability. This study aims to describe the accountability of managing village funds in Peliatan Village, Gianyar. The selected informants are informants who are involved in village fund management consisting of the village head, village secretary, financial officer, planning officer and chairman of the BPD. The data analysis technique uses the Miles and Huberman model with an interpretive paradigm. The results of the study show that accountability for village fund management planning is carried out in a participatory and transparent manner. Accountability for the implementation of village funds is guided by the APBDes and carried out using the ngayah system. Accountability for the realization of village funds is reported to the Regent, PMD and the community. Information to the public is conveyed through regional heads, billboards, and social media. Keywords: Accountability; Management Village Fund.